2249. Insulin Resistance Is Associated with Higher Viral Loads Among HIV-1-Infected Patients Initiated on 12 Months of First-Line Antiretroviral Therapy. (26th November 2018) - Mulenga, Lloyd; Musonda, Patrick; Chirwa, Lameck; Siwingwa, Mpanji; Phiri, Henry
Abstract: Background: As HIV-infected patients are living longer due to ART and decreasing mortality, the burden of noncommunicable diseases (NCDs) is expected to rise. With the implication of Insulin resistance (IR) and inflammation in the pathogenesis of Diabetes Mellitus (DM), DM is likely to be increasing in the HIV-infected patients in the Sub-Saharan Africa (SSA). HIV is characterized with systemic inflammation and markers which quickly decrease with ART initiation regardless of type of ARV regimen though they do not normalize. We thus assessed the relationship between IR and Virologic treatment failure among HIV-1-infected individuals at 12 months of first-line ART in the Zambian ART program. Methods: We conducted a cross-sectional survey among HIV-1-infected individuals at 12 months (±3 months) of first-line ART. Systematic sampling was performed and 20 clinics were selected based on the random starting-point, sampling interval and cumulative population size giving a sample size of 460. Eligible patients had their fasting blood specimens collected for VL, insulin, blood glucose, high sensitive c-reactive protein (hsCRP), tumour necrosis factor alfa (TNFa) and Lipogram. Anthropometric indices were also measured including visceral fat. Insulin resistance (IR) was determined using Homeostatic model assessment (HOMA). Proportions for each outcome at linearized standard error 95% confidence interval and summary estimates were determined. Viral Load suppression (VLS) was defined according to the detection threshold which was <20 copies/mL and treatment failure was defined as VL > 1, 000 copies/mL. Results: Of the 473 patients enrolled, 142 (30%): 95% CI (26%, 34%) had IR. 19% of Individuals with IR had treatment failure compared with 5.7% with treatment failure and without IR ( P -value < 0.0001). Treatment success was associated with less likelihood of IR (OR 0.26 (0.14, 0.48), P -value < 0.0001. Among individuals with VLS, 82, out of 142 (58%) 95% CI (0.54%, 0.70%) had IR compared with 232 out of 331, (70%) 95% CI (65%, 75%) who did not have IR ( P -value = 0.042) Conclusion: Patients with poor virological outcomes at 12 months of first-line ART had increased likelihood of insulin resistance compared with those with treatment success. There was good evidence to suggest that the proportion of those with VLS and IR was less than those with VLS and no IR. Disclosures: All authors: No reported disclosures.